Environmental factors related to quality of life of parents of children with autism spectrum disorder: a scoping review - Amy Azira Hamis,; Roszita Ibrahim,; Mohd Hasni Ja’afar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Concerns about the quality of life (QoL) of parents of children with autism spectrum disorder have been raised by previous study. Policy decision-makers and healthcare professionals can be better informed about the environmental factors associated with parental QoL, which will enhance outcomes for both parents and children. The objective of this review is to perform a comprehensive review that assesses the environmental relevant factors associated with quality of life (QoL) of parents of ASD children (under 18 years old). To identify the environmental factors associated with parental QoL, a scoping review was conducted using the Arksey and O'Malley original and enhanced framework. Three electronic database (PubMed, Scopus & WOS) and reference list checks were used in the search. Social support, family support, residential condition, and access to services were all factors linked to the parental quality of life in this group. The review highlighted environmental factors as one of the variables that have an association with parental QoL. The results of this analysis also highlighted potential areas of support that have implications on future policy and practices.